PENGARUH PEMBERIAN ZEOLIT DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH DI KABUPATEN BREBES - Mohamad Amin; M. Al-Djabri (Universitas Muhammadiyah Semarang, 2017)
Onion crop is one of the products featured pertaian Brebes. Shallots have a function as a seasoning used each day by the public and as a raw material medicines, so the demand for onion is always increased with population growth. The increasing needs of onion should be balanced by an increase in production, so Brebes can still support the products of onion at the national level reached 23% and to the level of Central Java Province reached 40%. With the reduction of agricultural land onionfor toll roads (+ 200 ha) and the physical and chemical damage as a result of the use of pesticides and fungicides excessive red onion productivity stagnant for the last five years with an averageproductivity of 10.2 tonnes / Ha. The application of zeolites and coop cow manure have been done in the field of agriculture like rice, carrots, eggplant, and apples at a ratio results ranged from 106% to 163% for the rice to carrots. While the shallot farming application of zeolites has not been done.In this study proves that the use of 1 ton / ha zeolite productivity of shallot reached 18.86 tonnes / ha or increase productivity of 2.32 tonnes / ha or 12.12% of the dick (16.54 tonnes / ha), so the net gain Rp. 193 202 100, - or 32.07% of net clappers on dick (Rp. 131 243 200, -). Key ward : onion, zeolit, coop cow manure